The Inheritance of Women: Stolen Money and Refunded Rights (Journal of the College of Education for Women, 2019)
Praise be to Allaah Mahmoud every tongue, the idol of all time, which is not withouthis knowledge everywhere, not occupied like for like, most of all likes and peer, and picnicfor wife and children, and carried out his reign in all the subjects, neither representative by thebrains to think, nor fancy hearts photography, (is not nothing like Him, He is the All-Seer),and prayer and peace be upon the Messengers Muhammad and his family and companionsand followed them in truth until the Day of Judgment.After…..Has spoken in this search for The inheritance of women before and after Islamlegislative provisions which, because of its importance to show the right of women's rights,which began Msluba before Islam and was re-Islam, to see the vast difference between thetwo periods and how Islam took into account this important segment of the community but it'sa particular community.We have divided the research into four sections include demands as follows:First topic: the two demands and we talked about the legacy of the two women before Islamand in some contemporary societies and then we had a comparison between them.The second topic: It also includes two demands Pena during which evidence of the legalityof the legacy of women in Islam, and the wisdom of inheritance for women legislation.The third topic: We reviewed it in detail cases in which inherit their women and in all ofthose cases, and cases in which women withhold withholding decrease or withholddeprivation.The fourth topic: separated the cases in which women inherit the man, and cases in whichwomen inherit less or more or equal to the man or woman does not inherit the man inherits.Then the finale.